PENGARUH PENAMBAHAN PASIR BESI TERHADAP KUAT TEKAN BETON K-300 - Agusri, Erny; A Rivai, Masri (Universitas Muhammadiyah Palembang, 2019)
The purpose of this study was to determine the effect of iron sand on the K-300 concrete compressive strength. Iron sand added with a variation of 2-4% using cube-shaped specimens with dimensions of 15 × 15 × 15 cm as many as 27 samples consisting of 3 variations, each with 9 samples, concrete quality tested at 3, 7, and 28 days. The results showed the compressive strength of normal concrete characteristics at 3 days of age was 238.76 Kg / cm2, 7 days was 270.64 Kg / cm2, and 28 days was 370.16 Kg / cm2, the addition of iron sand was 2% at 3 days amounting to 192.33 Kg / cm2 with an effect of -6.11%, 7 days amounting to 262.14 Kg / cm2with an effect of -3.87%, 28 days at 314.77 Kg / cm2 with an influence of -11.8%, addition of iron sand 3% at 3 days at 207.88 Kg / cm2 with an effect of -14.65 %, 7 days amounting to 262.28 Kg / cm2 with an effect of -4.94%, 28 days at 296.64 Kg / cm2 with influenceat -16.8%, the addition of 4% iron sand at 3 days at 178.06 Kg / cm2 with an effect of -14.97%, 7 days at 236.13 Kg / cm2 with an effect of -10.3% 28 days at 264.58 Kg / cm2 with an effect of -26.2%. based on the results of the study it can be concluded that the more iron sand we use, the more there is a decrease in the concrete compressive strength